Role of serotonin, estrogen, and TNF-α in the paroxetine-impaired steroidogenesis and testicular macrophages polarization - Beltrame, Flávia Luciana; Moysés, Thiago Henrique Pereira; Coelho, Mônica Pereira; Steinvascher, Maria Clara Rossetto [UNESP]; de Oliveira, Salmo Azambuja; da Silva, André Acácio Souza; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP] (Wiley, 2024)
Background: Paroxetine, a selective serotonin reuptake inhibitor (SSRI) antidepressant, has caused male sexual dysfunction; however, the paroxetine mechanisms of action in testes are still unclear. Objectives: Paroxetine serotonergic effects in testes were evaluated, focusing on steroidogenesis and the correlation between macrophages population and possible TNF-α-derived oxidative stress. We also verified whether the changes are reversible following treatment interruption. Materials and methods: Adult rats received paroxetine (PG35 and PG65) or tap water (CG) for 35 days. PG65 was maintained without treatment for 30 more days. Intratesticular testosterone (IT), nitrite, and malondialdehyde concentrations were measured. To confirm serotonergic and estrogenic effects, Htr1b and Esr1 expressions were analyzed. The daily sperm production (DSP), frequency of abnormal seminiferous tubules (ST), SC number, ST area, and Leydig cells nuclear area (LCnu) were evaluated. TUNEL+ germ cells, M1 (CD68+), and M2 (Perls+) macrophages were quantified. 17β-HSD7, CYP19A1, NDRG2, oxytocin, TNF-α, and iNOS were evaluated by immunoreactions. Oxytocin and NDRG2 protein levels as well as Tnfa mRNA expression were also analyzed. Results: The Htr1b downregulation in testes confirmed the paroxetine serotonergic effect. The testicular sections showed abnormal ST frequency, ST atrophy and reduction of DSP, LCnu, SC number and Perls+ macrophages. TUNEL+ germ cells and LC were associated with strong NDRG2 immunoexpression. Paroxetine reduced IT levels and 17β-HSD7 immunoexpression in parallel to increased CYP19A1, oxytocin, TNF-α and iNOS. Esr1 and Tnfa overexpression and increased number of CD68+ macrophages were also observed together with high nitrite and malondialdehyde levels. Most parameters were not recovered in PG65. Conclusions: Paroxetine serotonergic effect impairs LC steroidogenesis, via aromatization, increasing estrogen/testosterone ratio, which in turn upregulate NDRG2, promoting apoptosis, and impairing sperm production. Serotonin–estrogen pathways may be responsible for M2/M1 polarization, Tnfa upregulation, and induction of oxidative stress. The unrecovered testicular changes after treatment discontinuation are due to persistent paroxetine serotonin/estrogen effects.
Keywords: apoptosis; Leydig cells; nitric oxide; SSRI; testosterone